Approaches to Address Malnutrition among Children: a Systematic Review - Nirmala Kusumaningrum Sunaryo; Hakim Tobroni HR; Elfi Quyumi Rahmawati; Fresty Africia (Journal of Global Research in Public Health, 2026)
Childhood malnutrition is a major public health problem associated with increased illness and death in children. Its effects may occur early, including disease, disability, and mortality, or persist long term, resulting in impaired cognitive development, higher disease risk, and reduced economic productivity. Malnutrition arises from a complex interaction of nutrition specific factors such as inadequate dietary intake, poor feeding and caregiving practices, and infectious diseases and nutrition sensitive factors, including food insecurity, limited caregiving resources, poor access to health services, and unhealthy living environments. Therefore, reducing childhood malnutrition requires the effective integration of both nutrition-specific and nutrition-sensitive interventions. The purpose of this systematic review is to determine the intervention strategies in addressing childhood malnutrition.  The research design used was the Systematic Review method. Science direct, Pubmed, Proquest, Google Scholar was data based which was used in article search. The articles obtained were filtered based on full text, 20 articles were found, and ten articles were analyzed through analysis of objectives, suitability of topics, research methods used, characteristics of respondents, and the results of each article, published 2013-2024, in English and Indonesia.  Intervention strategies in addressing malnutrition in childhood could be education, homebased therapy, and nutrition therapy. Education, homebased therapy, and nutrition therapy could manage of malnutrition in childhood.